A human macrophage – hepatocyte co-culture model for comparative studies of infection and replication of Francisella tularensis LVS strain and subspecies holarctica and mediasiatica. Issue 1 (December 2016) - Rennert, Knut; Otto, Peter; Funke, Harald; Huber, Otmar; Tomaso, Herbert; Mosig, Alexander
Abstract Background Francisella tularensis, a gram-negative bacterium replicates intracellularly within macrophages and efficiently evades the innate immune response. It is able to infect and replicate within Kupffer cells, specialized tissue macrophages of the liver, and to modulate the immune response upon infection to its own advantage. Studies onFrancisella tularensis liver infection were mostly performed in animal models and difficult to extrapolate to the human situation, since human infections and clinical observations are rare. Results Using a human co-culture model of macrophages and hepatocytes we investigated the course of infection of threeFrancisella tularensis strains (subspeciesholarctica – wildtype and live vaccine strain, andmediasiatica - wildtype) and analyzed the immune response triggered upon infection. We observed that hepatocytes support the intracellular replication ofFranciscella species in macrophages accompanied by a specific immune response inducing TNFα, IL-1β, IL-6 and fractalkine (CX3CL1) secretion and the induction of apoptosis. Conclusions We could demonstrate that this human macrophage / hepatocyte co-culture model reflects strain-specific virulence ofFrancisella tularensis . We developed a suitable tool for more detailed in vitro studies on the immune response upon liver cell infection byF. tularensis .